Enantioselective organocatalytic Michael additions to acrylic acid derivatives: generation of all-carbon quaternary stereocentres. - Rigby, C; Dixon, D (2008)
Acrylic esters, thioesters and N-acryloyl pyrrole have been identified as effective electrophiles in the enantioselective Michael addition reaction with beta-keto ester pro-nucleophiles catalysed by a cinchona alkaloid derived bifunctional organocatalyst; enantiomeric excesses of up to 98% and yields of up to 96% can be obtained for a range of Michael acceptors and pro-nucleophiles.